JOB SEARCH SYSTEM USING INTELLIGENT AGENT - sushmitha, Boini sri (The journal of contemporary issues in business and government, 2022)
Finding jobs that best suits the interests and skill set is quite a challenging task for the job seekers. The difficulties arise from not having proper knowledge on the organization’s objective, their work culture and current job openings. Summer jobs are becoming year-round side work. Even I’m rolling up my sleeves on the path of researching the best apps that will put to work on tasks, jobs and chores in one’s extra time. We set the hours and the amount of time you want to carve out for this side work. An app for finding small paid work in your local area. It is for users who are in need of some quick cash and willing to do small works like repairing a computer, babysitting, mowing a lawn and other similar tasks.